A Review of Plea Bargain Concept in the Anti- Corruption War in Nigeria - Adebayo, Akintunde (Brawijaya Law Journal, 2018)
This article aims to reviews corruption in Nigeria, the  plea bargain concept, the application of plea bargain in the war against corruption in Nigeria and concludes with recommendations. Corruption in Nigeria has become endemic. There is consistent desecration of societal values with serious economic and socio-political consequences. The Nigerian government over the years has put in place several measures to combat the menace called corruption. A number of anti-corruption agencies including Economic and Financial Crimes Commission (EFCC), Independent Corrupt Practices and other Related Offences Commission (ICPC), among others have been established in order to achieve this aim. In order to address the criticism and contentions associated with the concept under the EFCC Act, the Administration of Criminal Justice Act (ACJA) was enacted in 2015. ACJA makes elaborate provision for plea bargain so as to enhance quicker dispensation of justice and help in prison decongestion. This paper begins with brief description on anti corruption scheme established in Nigeria and endeavors to assess the strength of Nigeria's effort in plea bargain in the war against corruption, effective implementation, and compliance